The Passage Characteristics and Potential of Mbah Wajib Cave in Tambakrejo Village - Sumbermanjing Wetan District – Malang Regency - Alfi Sahrina; Heni Masruroh; Fatiya Rosyida; Febrian Arrya Withuda; Devi Prasetyo; Mohammad Ainul Labib; Galih Sukoco; Andika Aulia Ahmad (Universitas Pendidikan Indonesia, 2023)
The cave passage is a natural form that develops in karst area. The cave passage is the sign of karst development. Mbah Wajib cave is located in southern mountains of Malang regency. There are certainly few studies of it, so the aim of this study is to find out the characteristics of the passage and the potential existed in this cave. Geomorphological approach became important in identifying the characteristic and the potential of this cave. Speleomorphology analysis and surface topographic features identification were used to get information related to the surface and subsurface. Morphometric analysis was used to show the dimension and levels of the cave passage. Cave passage interpretation was used to get the patterns developed on the cave passage. The measurement result in the field showed that the condition of Mbah Wajib cave passage is dominantly wide in shape rather than high. Meanwhile, the cave morphometric analysis showed that the cave is in unconfined condition. The morphometric index showed that the cave has a large complexity with a combination of vertical and horizontal passages. The development of the cave passage is dominated by structural and hydrological control which is adjacent to the rock layers. Water flow input comes from closed basins or ponds that assemble inside the cave. The development of cave level showed that there are three levels; first, a phreatic passage; the second level is an epiphreatic condition which is a fluctuation in the groundwater level; the third level is developing a vadose passage